Introduction to psychology - Plotnik, Rod (Thomson/Wadsworth, 2008)
Like reading a magazine-not studying from a text-Plotnik's PSYCHOLOGY, 8e International Edition will draw you in and show you how visual and exciting the study of psychology can be. Rod Plotnik's modular, visually-oriented approach to the fundamentals of psychology makes even the toughest concepts engaging and entertaining. Incorporating the latest research updates, the text breaks concepts down into small, easily digested chunks that give you and great flexibility how you approach and study the subject